An Unexpected Province: The History of the Roman Province of Asia from 133 B.C. to 128 B.C. - Snowdon, Michael (My University, 2005)
This study follows the early years of the Roman province of Asia from the death of Attalus III, the last king of Pergamon, to the final defeat of Aristonicus and the annexation of the territory in 128. Despite the volume of scholarly work on facets of this subject, there remain gaps in our knowledge and a comprehensive study on the topic as a whole is required. The bequest of Attalus III was one of the more extraordinary events in Republican history, but it was not without cause. The first chapter focuses on the history of Roman-Pergamene relations, the character of Attalus III, and his will, in order to put the broader study into context. The second chapter deals with the crucial year 133 Be, when Aristonicus began his remarkably successful bid for the Pergamene crown, and the Roman Senate decided to grant freedom to the entire former kingdom. The third chapter deals with recently published epigraphic material from Metropolis, Pergamon, Caria and Phrygia to sort out fine, but important issues of chronology that help to explain Rome's eventual annexation of the territory. The chapter concludes with a discussion of when and why Rome chose to annex the former kingdom.
Keywords: Classics; Classics